The effect of insecticide synergist treatment on genome-wide gene expression in a polyphagous pest. Issue 1 (December 2017) - Snoeck, Simon; Greenhalgh, Robert; Tirry, Luc; Clark, Richard; Van Leeuwen, Thomas; Dermauw, Wannes
Abstract Synergists can counteract metabolic insecticide resistance by inhibiting detoxification enzymes or transporters. They are used in commercial formulations of insecticides, but are also frequently used in the elucidation of resistance mechanisms. However, the effect of synergists on genome-wide transcription in arthropods is poorly understood. In this study we used Illumina RNA-sequencing to investigate genome-wide transcriptional responses in an acaricide resistant strain of the spider miteTetranychus urticae upon exposure to synergists such as S, S, S-tributyl phosphorotrithioate (DEF), diethyl maleate (DEM), piperonyl butoxide (PBO) and cyclosporin A (CsA). Exposure to PBO and DEF resulted in a broad transcriptional response and about one third of the differentially expressed genes (DEGs), including cytochrome P450 monooxygenases and UDP-glycosyltransferases, was shared between both treatments, suggesting common transcriptional regulation. Moreover, both DEF and PBO induced genes that are strongly implicated in acaricide resistance in the respective strain. In contrast, CsA treatment mainly resulted in downregulation of Major Facilitator Superfamily (MFS) genes, while DEGs of the DEM treatment were not significantly enriched for any GO-terms.